(untitled) (International Journal of Engineering and Computer Science, 2017)
In wireless sensor network energy consumption plays major role .The main reason for designing a enhanced optimized energy efficient routing protocol is to reduce the scarcity of energy resource .The major intension of this protocol is to improve the data accuracy, packet delivery ratio and to reduce the retransmission delay, energy consumption using energy aware activity scheduling algorithm .The opportunistic routing make use of a scheduler to co-ordinate transmission .The need for a scheduling algorithm to perform multitasking and multiplexing performance .The proposed EOEERP reduces/eliminates such individual node formation and improves the overall network lifetime when compared with the existing protocols .It can be achieved by applying the concepts of energy aware activity scheduling algorithm for buffer node formation and routing respectively